Les effets d’un cours traitant de l’école inclusive sur les croyances de futurs enseignants au regard de leur sentiment de compétence en éducation inclusive - Langevin, René; Laurent, Angélique; Larivée, Serge; Sénéchal, Carole (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
The goal of this study, which was of an exploratory nature, was to evaluate the effects of an inclusive school course in which future teachers had the opportunity to systematically examine their own beliefs on the subject of inclusive education. For this purpose, two groups were formed: one experimental group (N = 25), which took the modified course, and one control group (N = 25), which took the same course but without modifications. At the beginning and at the end of the course, the two groups filled out a questionnaire on the subject of their beliefs about inclusive education. The statistical analysis carried out on the total score suggests that the experimental group did not obtain a significantly higher score than the control group did except in the domain of pedagogical competencies and leadership. Also, after having completed the modified course, the future teachers in the experimental group declared themselves to be more competent than those in the control group for the questionnaire items pertaining to seven out of eight indicators from the competence 4 norms of Alberta Education (MEA, 2018). Curiously, the future teachers from both groups felt incompetent with classroom management (indicator 6) whether they followed the modified course or not. These results seem promising, since they would indicate an interesting way of helping future teachers augment their feelings of competence in the area of inclusive education by means of a university course. Keywords: modified school inclusive course, future teachers, beliefs about inclusive education, feelings of competence